METHODOLOGY OF TEACHING INFORMATICS IN PEDAGOGICAL UNIVERSITY (European Journal of Interdisciplinary Research and Development, 2023)
What is informatics? What are its main contributions, and which results of informatics are fundamental knowledge about the functioning of our world? Why should computer science be part of the school curriculum and which topics should be introduced? How does teaching informatics contribute to the pupils’ way of thinking? In this article, we search for possible answers to these questions.